Theoretical and conceptual principles for making Universal Access to Knowledge in Mexico. - Esquivel-Hernández, Marco Antonio; Escudero-Nahón, Alexandro (Revista Pensamiento Americano)
Introduction: Universal Access to Knowledge (AUC) is a recently promoted term by the National Council of Humanities, Sciences and Technologies (CONAHCYT) of Mexico, but there is no clear guide to realise it. Therefore, there is a need for an AUC model with best practices for the expansion of science in society. Objective: to present in a clear and concrete way a set of theoretical, conceptual and procedural principles that are useful to carry out AUC in the Mexican context. To this end, it is necessary to describe that scientific communication is divided into two main categories: dissemination, which presents findings from the scientific field among specialists, and popularisation, which shares science with the general public. The AUC is an emerging science outreach strategy that is governed by principles of open access and horizontal communication to promote interest in science among all people. Reflection: In such a way that, this proposal is headed by the mentioned concepts and the fundamentals of graphic and audiovisual design are added to better face the challenge of making AUC. This open and horizontal approach to communicate science to the non-specialist public will be useful to define what Universal Access to Knowledge is and how to carry it out, as well as to consolidate the scientific community as a key part of society and to boost the interest of children and young people in scientific research.